LITERATUR ‘ULUM AL-QUR’AN ULAMA INDONESIA DAN TIMUR TENGAH: STUDI PERBANDINGAN KARYA AHSIN SAKHO MUHAMMAD DAN MANNA’ ALQATHTHAN - Nur Hazfira, Annisa; Mursyid, Ali (Moderation | Journal of Islamic Studies Review, 2022)
The discussion of the 'ulum Al-Qur'an is very broad, complicated, with Arabic literature that is difficult to understand. The existence of the book "Embracing Ulumul Qur'an" by Ahsin Sakho Muhammad which is unique, is interesting to study. This article examines Ahsin's work, by comparing it with the literature of 'ulum Al-Qur'an by Manna' al-Qaththan, which is widely used as a reference in Al-Qur'an and Tafsir Study Programs, in several universities, both at home and abroad. The main focus discusses: (1) the similarities and differences of the 'ulum Al-Qur'an in the book Membumikan al-Quran by Ahsin Sakho Muhammad and in the book Mabahits fi 'ulum AlQur'an, by Manna' al-Qaththan, 2) How is the explanation and discussion of Qira'ah and Rasm in general in these two works? This type of library research seeks to analyze descriptively-comparatively. The result, concludes the following: First, examines the material related to the 'Ulum Al-Qur'an. Second, on the material of science Qira'ah and Rasm. The similarity of the works of these two figures is in describing in general the definitions of the three materials discussed, as well as in citing examples usually taking from a number of verses of the Qur'an which are then given explanations and similarities in the reference sources. Meanwhile, the difference between the two is the scope of the discussion and the topics discussed from each theme. Ahsin Sakho always provides relevance to Muslims in Indonesia, while Manna' Al-Qaththan only focuses on the core of the topics discussed.